Akuntabilitas berdasarkan amanah pada UMK makanan dan minuman tersertifikasi halal - Puri Kharisma Nuraini; Mohammad Nizarul Alim (Journal of Halal Industry Studies, 2025)
This study aims to demonstrate the importance of balance that not only considers individual interests but also prioritizes the interests of various stakeholders, including God, humans, and the environment. This study also provides in-depth information on the implementation of trust-based accountability in MSEs following the acquisition of halal certification. This study employs a qualitative approach, utilizing data collection methods that include interviews with business actors in MSEs, which will serve as the sample. The research data used in this study are primary, specifically the results of interviews. The results show that Micro and Small Enterprises (MSEs) in Bangkalan and Surabaya have implemented the principles of Sharia Enterprise Theory. The practice of trust-based accountability implemented by business actors in the Bangkalan and Surabaya areas aligns with the values of Islamic teachings. However, the method of financial recording by business actors has not been done formally or structured. Meanwhile, based on a phenomenological approach, trust-based accountability in the halal certification process is driven by two main factors: regulatory factors and economic factors.